Cardiac involvement in dengue infection - Mitrakrishnan C Shivanthan; Mitrakrishnan R Navinan; Godwin Roger Constantine; Senaka Rajapakse (Journal of Infection in Developing Countries)
Introduction: Dengue is endemic in the tropics, and complications involving organ systems are seen with varying incidence. Methodology: We performed a systematic review. MEDLINE, EMBASE, Scopus SciVerse, Google Scholar, and LILACS were searched for papers providing information on cardiac involvement in dengue. Results: Cardiac involvement is not uncommon in dengue infection and is often transient, but may be associated with significant morbidity and even mortality. Direct viral invasion, immune mechanisms, electrolyte imbalance, derangement of intracellular calcium ion storage, lactic acidosis, and ischemia due to hypotension all play a role in myocardial dysfunction. The manifestations of cardiac involvement include clinical, electrocardiographic, echocardiographic, cardiac enzyme, and histopathologic abnormalities. Echocardiography appears to be a useful tool for detecting myocardial involvement and should be performed in patients with electrocardiographic abnormalities or hemodynamic instability. Treatment is largely supportive, though there are some anecdotal reports of improvements with specific agents. Conclusions: Knowledge on cardiac manifestations in dengue is limited, and further studies are needed to establish the exact pathophysiology and role of specific agents in the prevention and treatment of cardiac complications in dengue.